2010
DOI: 10.1039/b9nr00306a
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of carbon nanotube-reinforced epoxy resins

Abstract: Nanocomposites of cured epoxy resin reinforced by single-walled carbon nanotubes exhibit a plethora of interesting behaviors at the molecular level. We have employed a combination of force-field-based molecular mechanics and first-principles calculations to study the corresponding binding and charge-transfer behavior. The simulation study of various nanotube species and curing agent configurations provides insight into the optimal structures in lieu of interfacial stability. An analysis of charge distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…[2][3][4][5] Epoxy resins have been widely used in the fields of coating, adhesives, and electronics because of their high adhesive strength, mechanical properties, dimensional stability, and chemical resistance. 6,7 However, epoxy resins are relatively brittle and often display low fracture toughness (K IC ), which has hindered some of their applications. [8][9][10] Toughening modification of epoxy resins has been intensively studied in the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Epoxy resins have been widely used in the fields of coating, adhesives, and electronics because of their high adhesive strength, mechanical properties, dimensional stability, and chemical resistance. 6,7 However, epoxy resins are relatively brittle and often display low fracture toughness (K IC ), which has hindered some of their applications. [8][9][10] Toughening modification of epoxy resins has been intensively studied in the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…15 Their calculation indicated that the resin EPON-862 with curing agents could adopt helically wrapped conformations around SWCNTs. They also showed that the number of aromatic rings in the curing agent influences the overall stability of the nano-reinforced composite.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin is one of the most important thermosetting resins used in various application fields due to their attractive properties such as high modulus, low curing shrinkage, good chemical resistance, and high adhesion. [1][2][3] However, the high cross-linking density of cured epoxy resins leads to a highly undesirable property, that is, they are notoriously brittle, which causes poor tolerance to impact and thus hinders their practical applications for high-performance composites. To overcome this problem, researchers have been devoted to develop various methods to toughen epoxy compounds.…”
Section: Introductionmentioning
confidence: 99%